Immunohistochemical activity of Prohibitin-2 and Stomatin-Like Protein-2 in patients with ulcerative colitis - Küçük, İrfan and Tanoğlu, Alpaslan and Öncü, Kemal and Yılmaz, İsmail and Kara, Muammer and Beyazıt, Yavuz and Akyol, Taner and Kaplan, Mustafa and Özarı, Halil Onur and Yazgan, Yusuf (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: We aimed to semi-quantitatively investigate prohibitin-2 (Phb-2) and stomatin-like protein-2 (Slp-2) expressions in patients with ulcerative colitis (UC) and healthy controls using the immunohistochemical (IHC) method. We also aimed to evaluate the correlations between the activity of UC and the expressions of these two proteins. Materials and Methods: Ninety-five patients with UC (82 males and 13 females) and 38 healthy controls (35 males and 3 females) were included. Clinical and endoscopic activities of UC were assessed. Conventional laboratory activation parameters and severity of inflammation measures were used for the evaluation of histological activity. IHC staining of biopsy samples for the two proteins were semi-quantitatively applied, similar to previously described methods for colon adenocarcinomas. Results: IHC scores of Phb-2 were lower but Slp-2 scores were higher in the UC group than in the healthy controls (p<0.05 and p=0.003, respectively). Phb-2 scores were positively correlated with clinical and histological activities (r=0.364, p<0.05 and r=0.220, p<0.032, respectively). In the UC group, endoscopic activity scores, C-reactive protein levels, and sedimentation rates were also positively correlated with Phb-2 scores (r=0.279, p<0.05, r=0.216, p<0.05, and r=0.216, p<0.05, respectively). IHC scores of Slp-2 were not significantly correlated with the activity parameters of UC. However, there was a significant positive correlation between the expressions of Phb-2 and Slp-2 proteins (p<0.001). Conclusion: Phb-2 may serve as a valuable new biomarker for predicting the severity of all UC activity parameters. The therapeutic effectiveness of both Phb-2 and Slp-2 should be taken into consideration.